MULTI-CRITERIA GIS ANALYSES WITH THE USE OF UAVS FOR THE NEEDS OF SPATIAL PLANNING - D. Zawieska; J. Markiewicz; A. Turek; K. Bakuła; M. Kowalczyk; Z. Kurczyński; W. Ostrowski; P. Podlasiak (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2016)
Utilization of Unmanned Aerial Systems (UAVs) in agriculture, forestry, or other environmental contexts has recently become common. However, in the case of spatial planning, the role of UAVs still seems to be underestimated. At present, sections of municipal development use UAVs mainly for promotional purposes (films, folders, brochures, etc.). The use of UAVs for spatial management provides results, first of all, in the form of savings in human resources and time; however, more frequently, it is also connected with financial savings (given the decreasing cost of UAVs and photogrammetric software). The performed research presented here relates to the possibilities of using UAVs to update planning documents, and, in particular, to update the study of conditions and directions of spatial management and preparation of local plans for physical management. Based on acquired photographs with a resolution of 3 cm, a cloud of points is generated, as well as 3D models and the true orthophotomap. These data allow multi-criteria spatial analyses. Additionally, directions of development and changes in physical management are analysed for the given area.